How do you normalize (-2i- 3j + 2k) (−2i−3j+2k)?
1 Answer
Mar 5, 2017
Explanation:
In normalizing the vector we are finding a unit vector (magnitude/length of one) in the same direction as the given vector. This can be accomplished by dividing the given vector by its magnitude.
u=v/(|v|)u=v|v|
Given
|v|=sqrt((v_x)^2+(v_y)^2+(v_z)^2)|v|=√(vx)2+(vy)2+(vz)2
|v|=sqrt((-2)^2+(-3)^2+(2)^2)|v|=√(−2)2+(−3)2+(2)2
|v|=sqrt(4+9+4)|v|=√4+9+4
|v|=sqrt(17)|v|=√17
We now have:
u=(<-2,-3,2>)/sqrt(17)u=<−2,−3,2>√17
Hope that helps!